Counter Terrorism : Case Study On The Radicals Religious Group - Eko Rubiyanto; Munsharif Abdul Chalim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This research aims to explore counter terrorism: a case study of radical religious group. This research used the normative juridical approach. Data collection techniques using data reduction, data presentation, triangulation and conclusion. The results showed that the group of religious radicalism in the jurisdiction of Bekasi police pioneered by asatidz or Imam FPI called for promotion of hatred toward religious groups. The media used in the spread of religious radicals in Bekasi Police Jurisdiction is through social media with the modus operandi of instilling the idea that Islamic law is the most correct. In recruiting, there are several methods used, including the cadre, mentoring, and mastery of places of worship with the main target is the younger age groups. Flourishing of religious radicalism caused by several factors, among others. Bekasi location of the region as a buffer capital city of Jakarta, the lack of supervision of the police, the involvement of religious leaders, the low education level of the community, as well as the economic conditions of the needy. Policing is done by Bekasi policecurrently done with prevention efforts, either through counseling activities, socialization, door to door system, coordination with Tomas, Toda, or Toga, as well as joint meetings FKUB about the dangers of radicalism and terrorism. The effort is still deemed less effective, so the Bekasi police in the future in the fight against terrorism must be put forward Counter Radicalization and Deradicalisation to strengthen four pillars of nationhood.Keywords: Radicalism; Terrorism; Religion.